Income Analysis of Vegetable Farmers in Lorulun Village, Wer Tambrian District, Tanimbar Islands Regency - Belalawe, Maria Lusia; Salakory, Melianus; Leuwol, Ferdinand Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
In research on the analysis of income of vegetable farmers. The type of research used is to use qualitative methods with description approaches. The location in this study is in the village of Lorulun District Wer Tambrian Regency Tanimbar Islands. The research time used is 1 month. The subject in this study is a randomly selected Vegetable Farmers Society using Purposive Sampling Technique. Based on the results of the research obtained then the results of research that the income of farmers and vegetable commodities in general with marketing systems sold to the market from the yield of spinach vegetables, kale vegetables and mustard vegetables with per bond of Rp.5,000. From this marketing result, obtained vegetable income spinach. kale and mustard in the market is sebessar Rp.55,000 per day while the income of spinach vegetable farmers, kale and mustardians per month amounting to Rp. <4.95,000.